Performing Template Matching Process for RLNS Based System in Binary Logic - Shalini, R. V. (New Approaches in Engineering Research Vol. 11, 2021)
This research work is the implementation of cross correlation operation that is used in template matching process for image or object detection. Digital image processing is used in various areas such as identification of natural resources, medical diagnosing procedures, satellite pictography etc. An image is a collection of minute information called as pixels. All manipulation operation in an image is done in these pixel values that makes image processing techniques more complicated. The design of image processing hardware demands more power dissipation and area. Residue Number System (RNS) based system is applied for image processing applications, which has additional advantage of encryption in data processing. As logarithmic number system reduces multiplication process to mere addition, template matching process is proposed in this work for Residue Logarithmic Number System (RLNS) based system. In this paper the methodology for performing template matching process is designed and compared with binary and ternary logic based existing design structures and validation for the optimum design technique in terms of area consumed, Total Power dissipation and delay is proposed.